PLANNING A LESSON TO CREATE AN EXCELLENT MATHEMATICS TEACHING - Sapa’at, Asep (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2010)
The pursuit of mathematics teaching excellence is about constantly reflecting on one’s teaching practices and actively seeking improvements in teaching for the purpose of ensuring that students are learning. The three main things of mathematics teaching excellence is about being effective in teaching design and delivery, student learn best through active construction of knowledge, and teaching can only be valued when the process and outcome are made transparent. An effective instruction is indicated by designing lesson plan well. The lesson plans should be suitable to the students’ characteristics and needs. Using qualitative methods with descriptive case study as its framework, three teachers’ lesson plans of mathematics teachers at SMART Ekselensia Indonesia were analyzed using theories that were adapted from National Council of Teachers of Mathematics Professional Standards (1991). The data were gained from documentation and interview. The three teachers’ lesson plans under study showed that the aspects taken into their lesson plan might contradict what were expected. It is indication that the teachers need improvement of how to formulate lesson plans properly.